To investigate the effects of the depth of golf ball dimple to its trajectory using CFD / Nik Mohammad Sukri Nik Soh - Nik Soh, Nik Mohammad Sukri (2010)
The purpose of having dimples on surface of golf balls is generally known to delay separation of boundary layer hence reduce the drag and make the ball fly higher and further distance, that's what a golfer wants!. While this is have been practiced around the globe, the detail explanations of how dimples help is remain a perfect debate topics among researcher and sport-scientist. The purpose of this study is to find out the effect of dimple depth to drag and trajectory of a golf ball using Computational Fluid Dynamic (CFD) simulation. The result is then represented in both graphical and data-graph plot. The result showed that drag and momentum is changed with the difference dimple depth, not in proportionate way but in unique way caused by turbulence created by different dimple depth.